(untitled) (Journal of Informatics Education and Research, 2024)
Research in job embeddedness (JE) has gained momentum in the last decade thanks to its growing popularity among scholars and practitioners. Job embeddedness (JE) theory emphasizes the critical decision factors that explain why employees are willing to stay (Allen).JE scholars have also studied the construct in the context of business and management. Scholars used Hofstede’s categorization of cultures as either individualist or collectivist to explain the need for various JE methods across nations, and the field has subsequently appeared to be developing. The ever-growing interest of JE scholars in Business and Management and cross-cultural scenarios requires a comprehensive and scientific review of the literature. The intellectual structure of job embeddedness research in business and management is mapped in this study using bibliometric analysis, filling a significant gap in the literature and offering future research options to researchers in this field.